2023
DOI: 10.1212/nxi.0000000000200092
|View full text |Cite
|
Sign up to set email alerts
|

Visually Evoked Potential as Prognostic Biomarker for Neuroaxonal Damage in Multiple Sclerosis From a Multicenter Longitudinal Cohort

Abstract: Background and ObjectivesWith the increasing use of visually evoked potentials (VEPs) as quantitative outcome parameters for myelin in clinical trials, an in-depth understanding of longitudinal VEP latency changes and their prognostic potential for subsequent neuronal loss will be required. In this longitudinal multicenter study, we evaluated the association and prognostic potential of VEP latency for retinal neurodegeneration, measured by optical coherence tomography (OCT), in relapsing-remitting MS (RRMS).Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Throughout our literature review, the vast majority of the previous EEG studies and research work were on VEP, and focused on analysing its latency and amplitude 737 for monitoring and diagnostic purposes. In the same vein, the second most frequently investigated evoked potential in EEG is MEP, whose latency, amplitude and any detected abnormalities have extensively been analysed and investigated 14, 20, 21, 25, 31, 32, 3845 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout our literature review, the vast majority of the previous EEG studies and research work were on VEP, and focused on analysing its latency and amplitude 737 for monitoring and diagnostic purposes. In the same vein, the second most frequently investigated evoked potential in EEG is MEP, whose latency, amplitude and any detected abnormalities have extensively been analysed and investigated 14, 20, 21, 25, 31, 32, 3845 .…”
Section: Resultsmentioning
confidence: 99%
“…Along the same lines, authors in 20, 21, 25, 28, 31 postulate that combined scores are a good predictor for EDSS in MS patients longitudinally. The detection of VEP from EEG signals was investigated, and the quantification of its amplitude and latencies between different MS patients were studied in 7, 15, 18, 23, 27, 37 . For that, authors in 7, 15, 18, 23, 27, 37 postulate that patient with multiple sclerosis (PwMS) have in average longer VEP latencies when their retinal fibres are below norm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional Visual Outcomes LCLA, assessed with the low-contrast Sloan letter chart, has greater sensitivity than high-contrast VA for detecting Confounding MWF registered myelin debris 112,113 and changes in total water signal 114 The orientation of WM tracts relative to main magnetic field influence MWF 115 MWF measurements were reproducible in healthy adults 116,117 MWF in total brain, lesions, and cervical cord have been shown to change over time in MS patients [118][119][120][121] Differences meaningful vision changes in MS 89 and has reported excellent interrater reliability. 90 The finding that LCLA was improved following treatment with immunomodulatory therapies 7,91 VEPs are reproducible across sites 135 VEPs are sensitive to longitudinal change in MS patients 85,135 Prolonged full-field VEP latency predicts subsequent disability progression 136 86,87 Changes in pRNFL and GCL/IPL can be readily detected following acute attacks of optic neuritis [139][140][141] and with subclinical injury 142,143 Changes in pRNFL and GCL/IPL are associated with changes in visual acuity and global and regional measures of brain atrophy [143][144][145][146][147][148][149] -LCLA Confounding LCLA is not specific to myelination of the visual pathway † LCLA has good interrater reliability 90 LCLA demonstrated changes over time in response to immunomodulatory therapies 7,91 LCLA correlates with brain lesion volume along the optic pathway, 150 validated measures of global...…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Importantly, current studies have demonstrated that VEP latency correlates with optic nerve demyelination and remyelination ( 21 ), and VEP recordings have been recently established as a valuable tool for studying neurodegeneration and testing neuroprotective drugs in the context of animal models of demyelination ( 22 , 23 ). VEP recordings also have potential prognostic value for subsequent retinal ganglion cell (RGC) loss in MS ( 24 ). Thinning of the retinal nerve fiber layer (RNFL) and RGC layer as measured by optical coherence tomography (OCT) imaging in MS patients over time are reliable indicators of structural RGC degeneration ( 25 , 26 ) Quantification of the macular ganglion cell layer/inner plexiform layer (IPL) thickness is currently the most used OCT marker to determine retinal atrophy in MS ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%